2012
DOI: 10.1037/a0026301
|View full text |Cite
|
Sign up to set email alerts
|

Preschool classroom behavioral context and school readiness outcomes for low-income children: A multilevel examination of child- and classroom-level influences.

Abstract: Guided by an ecological theoretical model, the authors used a series of multilevel models to examine associations among children's individual problem behavior, the classroom behavioral context, and school readiness outcomes for a cohort of low-income children (N ϭ 3,861) enrolled in 229 urban Head Start classrooms. Associations were examined between early problem behavior (overactive and underactive behavior) at the child and classroom level and three dimensions of school readiness: cognitive skills, social en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 128 publications
4
16
0
Order By: Relevance
“…Some consider the finding that classroom age composition does not relate to child outcomes surprising due to research that shows that peers are very influential on children’s classroom experiences (Bell et al, 2013; Bulotsky‐Shearer, Domínguez, & Bell, 2012; Hamre & Pianta, 2001). However, classroom age composition only accounts for the age of peers.…”
Section: Discussionmentioning
confidence: 99%
“…Some consider the finding that classroom age composition does not relate to child outcomes surprising due to research that shows that peers are very influential on children’s classroom experiences (Bell et al, 2013; Bulotsky‐Shearer, Domínguez, & Bell, 2012; Hamre & Pianta, 2001). However, classroom age composition only accounts for the age of peers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that children’s behavioral problems (e.g., internalizing and externalizing) relative to their classroom peers’ behavior problems predicted children’s academic outcomes, such as their social competence in school and academic achievement (e.g., Bulotsky-Shearer, Dominguez, & Bell, 2012; Figlio, 2007; Yudron, Jones, & Raver, 2014). Only one study, to our knowledge, has examined children’s EC relative to their classroom peers.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need for experimental work that may more precisely tease apart the mechanisms by which certain classroom processes and regulation-focused interventions may be effective for improving children's learning. Third, effect sizes from this study are small, as is typical of classroom-based research (e.g., Bulotsky-Shearer, Dominguez, & Bell, 2012;Hamre & Pianta, 2005;Reyes, Brackett, Rivers, White, & Salovey, 2012) as well as with studies of specific subsets of children from large representative samples (e.g., Adelson, McCoach, & Gavin, 2012). Fourth, although our measure of cumulative economic risk included the most robust indicators of economic disadvantage (i.e., income below poverty and mothers' education below high school; Crosnoe & Cooper, 2010), research suggests that there are other indicators related to economic risk, such as food insufficiency or household density, that may add meaningfully to our understanding of the impact of cumulative risk on children's outcomes (e.g., Burchinal, Vernon-Feagans, Cox, & Key Family Life Project Investigators, 2008).…”
Section: Limitationsmentioning
confidence: 99%